Perancangan Sistem Informasi Perpustakaan Berbasis Mobile pada Sekolah Swasta Nila Harapan - Panjaitan, Calvin Nicolas; Simamora, Roni Jhonson; Jamaluddin, Jamaluddin (Universitas Methodist Indonesia, 2025)
Sekolah Swasta Nila Harapan is an educational institution that also feels the importance of the development of such technology, especially in the library section, where the part of library must provide information about the book data, including in the borrowing of books in libraries that currently still use the manual system in the processing of the information system of libraries. Based on the need for faster data processing, it is necessary to design a mobile-based library information system. The result and discussion of the school library information system design is hybrid which means the system is built using the website used by the administrator and mobile used by Sekolah Swasta Nila Harapan. With the presence of a mobile-based library information system at Sekolah Swasta Nila Harapan, it can make it easier for officers to make book lists without having to make a book list physically, and also facilitates officers when carrying out the process of fines such as late return of books, as well as fines when the books are damaged or lost by students.